Spaces and Places to Play: The Formation of a Municipal Parks System in London, Ontario, 1867-1914 - Kossuth, Robert (Ontario History)

(untitled) (The Ontario Historical Society, 2005)
How a municipal parks system formed in London following Confederation provides insight into the struggle that existed between public recreation and those who championed its provision, and political leaders concerned with the expense of providing public parks. Victoria, Queen’s and Springbank Parks, all formed in the 1870s, provided Londoners with public spaces to recreate. Each park came into being for different reasons and served specific recreation and leisure roles. Not until the turn of the century, however, did growing pressure from external and internal social reform movements such as national playground initiatives lead London to organize their parks into a coherent system through the formalization of a recreation bureaucracy.